Respuesta :

Answer:

1.) Option C

2.) Option B

3.) Option D

4.) Option A

Step-by-step explanation:

[tex] \frac{3x {}^{2} }{y {}^{ - 3} } \\ [/tex]

Here, we know that

[tex]a {}^{ - 1} = \frac{1}{a} \\ [/tex]

So,

[tex] \frac{ {3x}^{2} }{y {}^{ - 3} } = \frac{ {3x}^{2} }{ \frac{1}{y {}^{ 3} } } = {3x}^{2} y { }^{3} \\ [/tex]

Thus, Option C is correct

2.)

[tex]( {4}^{0} )( {4}^{2} ) \\ [/tex]

We know that,

n⁰ = 1

where, n = any real number

So,

[tex]( {4}^{0} )(4 {}^{2} ) = 1 \times 16 = 16 \\ [/tex]

Thus, The answer is 16

3.)

[tex]( \frac{5}{3} ) {}^{ - 3} \\ [/tex]

We know that

[tex]a {}^{ - 1} = \frac{1}{a} \\ [/tex]

So,

[tex]( { \frac{5}{3} )}^{ - 3} = ( { \frac{3}{5} )}^{3} = \frac{27}{125} \\ [/tex]

Thus, Option D is correct

4.)

[tex] \frac{a {}^{2} {b}^{5}c {}^{0} }{ab {}^{7} } \\ [/tex]

[tex] \frac{a {}^{2} {b}^{5} c {}^{0} }{ab {}^{7} } = \frac{a}{ {b}^{2} } \\ [/tex]

Thus, Option A is correct

-TheUnknownScientist 72

ACCESS MORE